Production asymmetry of Ds from 600 GeV/c σ- and π- beam - Kaya, M. (2003)
The production of Ds- relative to Ds+ as a function of xF with 600 GeV/c Σ- beam is measured in the interval 0.15 < xF < 0.7 by the SELEX (E781) experiment at Fermilab. The integrated charge asymmetries with 600 GeV/c Σ- beam (0.53 ± 0.06) and π- beam (0.06 ± 0.11) are also compared. The results show the Σ- beam fragments play a role in the production of Ds-, as suggested by the leading quark model. © 2003 Elsevier Science B.V. All rights reserved.